How do policy environments influence technology adoption? Insights from Nigeria’s pod borer resistant (PBR) cowpea experience - Mockshell, Jonathan; Nwagboso, Chibuzo; Asante-Addo, Collins; Ritter, Thea; Zambrano, Patricia; Amare, Mulubrhan; Andam, Kwaw S. (International Food Policy Research Institute, 2024)
Policymakers are increasingly considering the promise of modern biotechnology, including genetically modified organisms (GMOs) to help solve development problems in health, agriculture, and other fields (Zambrano et al., 2022). However, debates persist around health and environmental implications (National Academies of Sciences, 2016; Raman, 2017; Smyth et al., 2021). The regulation of GMOs varies globally, with some countries implementing outright bans or imposing stringent controls (Sarkar et al., 2021; Yali, 2022). A recent study examines the Nigerian policy environment for Pod Borer Resistant (PBR) cowpea, which has been genetically engineered to resist the legume pod borer (Maruca vitrata) [Mockshell et al., (unpublished)]. Legume pod borers significantly reduce cowpea yield and quality, with losses of up to 80% reported (Andam et al., 2024; Mockshell et al., 2024). This policy note summarizes the findings of the paper, providing insights to guide policy development around the adoption of biotech food crops in Nigeria and other countries in Africa South of the Sahara (SSA). The primary research question is: Is there an enabling policy environment for PBR cowpea and what factors contribute to it?